The analysis of foreign systems of pension provision - Изекенова A. (Journal of Economic Research & Business Administration, 2017)
The article discusses the features of pension systems of some foreign countries - Australia, Finland, the Netherlands, Great Britain, the United States, Japan, Sweden, Chile, and Russia, which represent a combination of the three main institutions of pension provision. Firstly, social assistance as a tool to fight poverty in the developed countries. Secondly, compulsory pension insurance to reach the minimum required level of life in old age. Thirdly, individual voluntary insurance as a tool to accumulate funds on a voluntary basis for life support during the cessation of work activity. Also synthesized information about pension systems in different countries in the world. Results of Allianz Asset Management’s research, rated in the index of pension systems, are also analyzed in article.